Peer Observation : A Professional Learning Tool for English Language Teachers in an EFL Institute - Ejaz, Ahmed; Zaimuariffudin Shukri, Nordin; Sayyed Rashid, Shah; Mansoor Ahmed, Channa (Sciedu Press, 2018)
The key aim of this study is to explore the perceptions of English as foreign language (EFL) teachers about peer observation as a tool for professional development that is implemented in an English Language Institute of a Saudi Arabian university. This paper reviews literature on peer observation to develop a conceptual and theoretical understanding of peer observation systems in different contexts. It utilizes a mix-method approach and applies a questionnaire and semi-structured interviews as data collection tools. Questionnaire is used to get information about EFL teachers’ perceptions whereas semi-structured interviews provide an insight into their practices in the form of peer observation and future amendments for PD. The participants share their lived experiences who consider the current practice of peer observation a consistent professional challenge due to several factors, i.e. their lack of autonomy in deciding about the peers, trust deficit between administration and EFL teachers, rarely held pre-observation conferences due to the loads of teaching hours, observers’ insufficient training and qualifications in conducting PO, and the element of threat and insecurity. Based on the findings, recommendations are made to improve the existing peer observation system for the benefit of the EFL teachers, English language learners and the institute.